Rendering Self and Microagressions Visible Through the Shadow Image - Snepvangers, Kim (Imaginations)

(untitled) (York University, 2021)
This project, starting with Prompt 2 from the Massive Micro Sensemaking (MMS) led by Annette Markham and Anne Harris in May through June 2020, assisted me to move through the anxiety of COVID-19 lockdown. I set up four visual renderings—a series of photographs that, through a process of unfolding, make links to broader issues in my archival research in the context of settler colonial Sydney, Australia. Exploring lived experience through photography anticipates a creative a/r/tographic lens, focusing on rendering objects so that they take on a more-than-representational aspect, touching the materiality of objects as data. Adaptively layering the renderings moves beyond one dimensionality as a strict capturing of an observed phenomena. Here, an initial photograph has a latent, additional layer of shadow to build volume and re-cast semblances of the representational world through reflection.